Dermal IRF4+ dendritic cells and monocytes license CD4+ T helper cells to distinct cytokine profiles - Kerry L. Hilligan (Nature Portfolio, 2020)
Antigen presenting cells induce CD4+ T helper (Th) differentiation upon pathogen encounters. Here the authors use fluorescently-labeled bacteria, helminth and fungi to track and describe the functions of IRF4+ migratory type 2 dendritic cells and monocytes in the specific induction of Th1, Th2 or Th17 responses following skin inoculation.